PROSES INTEGRASI DAN IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGs) DALAM PENGENTASAN KEMISKINAN DI PROVINSI RIAU - Hasan Warso Syahputra (Jurnal Sumber Daya Manusia Unggul (JSDMU), 2021)
Riau Province Government considered to be foremost in preparation and planning for the implementation of SDGs in Indonesia. However, SDGs is an United Nation policy introduced into Riau Province development planning, the concept of SDGs can be in accordance with the direction of development policies and can also be something foreign, contradictory or even become a burden in its implementation in the regions. This study aims to see how the process of integration and implementation of SDGs in regional development, especially poverty alleviation in Riau Province, also revealed what obstacles were faced by the Riau Province government. This a qualitative descriptive research methods by collecting information in various ways such as direct observation, document review, recording and through direct interviews with selected informants from Regional Services that deal with poverty alleviation in Riau Province. The results showed that there were 17 indicators in Riau Province's RPJMD that were in line with SDGs indicators, and as many as 15 SDGs indicators that could be proxied into RPJMD indicators, while 217 indicators were not in the RPJMD and needed to be developed. In the RAD SDGs of Riau Province in 2017-2019 4 targets and 26 poverty SDGs indicators have been set which are supported by various programs implemented by several relevant services and other non-government parties.